Endemic Bamboo (Poaceae, Bambusoideae) of the Lesser Sunda Islands - I Putu Gede P. Damayanto; Himmah Rustiami; Miftahudin Miftahudin; Tatik Chikmawati (Jurnal Biodjati, 2023)
More than 40 species of bamboo were known from the Lesser Sunda Islands (LSI), including several endemic species. Endemic species are often highly specialized, found in limited geographical areas, and vulnerable to extinction if their habitat is destroyed. This study aimed to provide an account of endemic bamboo species on the LSI. Fieldwork involved collecting samples of bamboo in the LSI. Herbarium specimens of bamboo deposited in the Herbarium Bogoriense (BO), collected from the LSI were examined, and endemic LSI species were recorded. The conservation status followed the International Union for Conservation of Nature (IUCN) red list categories and criteria. The conservation status of unassessed species was evaluated using IUCN red list categories and criteria. A spatial analysis was also conducted. Data were analyzed and presented descriptively. There are 10 endemic bamboo species in the LSI, namely Bambusa ooh Widjaja & Astuti from Bali (conservation status: endangered), Chloothamnus reholttumianus (Soenarko) Widjaja from Sumba (vulnerable), C. schmutzii (S.Dransf.) Widjaja from Sumbawa and Flores (near threatened), Dinochloa kostermansiana S.Dransf. from Sumba and Flores (near threatened), D. sepang Widjaja & Astuti from Bali (vulnerable), Fimbribambusa rifaiana Widjaja from Alor (near threatened), Gigantochloa aya Widjaja & Astuti from Bali (vulnerable), G. baliana Widjaja & Astuti from Bali (vulnerable), G. taluh Widjaja & Astuti from Bali (vulnerable), and Schizostachyum purpureum Damayanto & Widjaja from Sumba (data deficient). They can be found at an altitude of 20–1700 m in various habitats, including forests, bamboo forests, villages, botanical gardens, along a road, slopes, valleys, riverbanks, and around a lake.